2013
DOI: 10.1177/0021998313479415
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment and adhesive bonding techniques for repair of high-temperature composite materials

Abstract: Adhesive bonding of structural aircraft materials depends upon a thorough understanding of factors that affect bond strength and durability. It is well known that surface preparation is critical to adhesive bond performance. However, little information is available regarding the effect of surface preparation procedures on adhesive bonding of high-temperature polyimide composites. Mechanical treatments such as hand sanding are commonly used for composite materials, and in general are known to improve the wettab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…It was observed that when the Al‐7075 surface was subjected to phosphoric anodizing, the hydrophilicity of the aluminum surface was increased remarkably as is observed in Figure 6C, due to the creation of a thin anodic porous layer of oxide on the surface. Similar findings were provided by Digby and Packham [ 24 ] and Dillingham et al [ 22 ]…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It was observed that when the Al‐7075 surface was subjected to phosphoric anodizing, the hydrophilicity of the aluminum surface was increased remarkably as is observed in Figure 6C, due to the creation of a thin anodic porous layer of oxide on the surface. Similar findings were provided by Digby and Packham [ 24 ] and Dillingham et al [ 22 ]…”
Section: Resultssupporting
confidence: 91%
“…A piece of non‐sticking, woven nylon fabric was used as a peel ply to impart a surface roughness on the composite surface during curing in the compression stage as suggested by Budhe et al [ 21 ] Sandblasting of the composite surface was carried out using 200‐μm silicon dioxide particles at an air blasting velocity of 2 mm/min for 1 min. The blasting angle was 75° and the nozzle to substrate surface distance was fixed at 450 mm while the blasting pressure was kept at 3 bars according to Dillingham et al [ 22 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural adhesive needed to satisfy the connection strength, as well as be able to fill the gap between panels. Scientific researches on structural adhesive connections are ongoing, and various structural adhesives are already available on the market (Mays and Hutchinson 1988;Dillingham et al 2014;Kumar, Patnaik, and Chaudhary 2017). For the actual projects, product maturity and construction convenience were also significant factors and thus, a commercially-available structural adhesive with a practical construction plan was required.…”
Section: Gfrp Panels and Purlins Connectionmentioning
confidence: 99%
“…Although water interactions with polymer surfaces were studied earlier [93], very little has been researched on the effect of surface types on bond performance in ABCJ's. Dillingham et al investigated on abraded and non-abraded composite surfaces and correlated their surface free energy with the bond strength [94]. In another study, Dillingham et al…”
Section: Surface Characterizationmentioning
confidence: 99%